Selective Neuronal Necrosis Associated with Status Epilepticus: MR Findings - Men, Suleyman; H. Lee, Donald; R. Barron, Jane; G. Muñoz, David (American Journal of Neuroradiology, 2000)
Summary: We present the MR imaging findings in an autopsy-proven case of selective neuronal necrosis involving the entire left cerebral hemispheric cortex, left thalamus, and contralateral cerebellum following a period of status epilepticus. Imaging findings include diffusion abnormality on diffusion-weighted images and increased intensity on T2-weighted images in the above-mentioned regions of the brain.